Collection of Elzevyres in Martynas Mazvydas National Library of Lithuania - Misiūnienė, Jadvyga (Knygotyra, 2006)
Elzevyrai (Elzevier) - the dynasty of Netherland publishers and printers who worked from the end of the 16th century till the beginning of the 18th century. During 129 years of their activity (1583–1712) they issued more than 2200 books and about 3000 scientific dissertations. The collection of elzevyrai in Martynas Mažvydas National Library of Lithuania consists of 231 books (180 titles). All elzevyrai kept in the collection are divided into two main groups: 1. True or authentic elzevyrai (158 titles); 2. False elzevyrai, i.e. imitations (21 title) and pseudoelzevyrai (the only one contrafaction). True, or original, elzevyrai are also divided into two groups: publications of Leiden (95 titles) and Amsterdam (63 titles) Elzevyrai companies. Among Leiden elzevyrai should be named Ebraicarum quaestionum by Johannes Drusius, sive Quaestionum ac responsionum libri duo (1583) – the first elzevyrai known; Acta synodi nationalis (1620) – the first book printed in the printing house of Isaak Elzevyrai with the signette of the "Anchoret"; Athanae Batavae ... libri duo (1625) by Johannes van Meurs, distinguished for its illustrations, as well as a series of Little Republics and a thesis from theology by Juzef Milecky printed in 1710 by Abraham Elzevyrai II, the last of Leiden Elzevyrai – the latest among elzevyrai kept in Lithuania. Among Amsterdam elzevyrai should be named Antiquae musicae auctores septem (1652), a digest prepared by Marcus Meibom, rare and valued edition; Corpus juris civilis (1663, in folio) – one of the best Amsterdam elzevyrai, as well as Historia critica Veteris Testamenti, printed in 1681 in the printing house of Daniel Elzevyrai’s widow, the last Amsterdam elzevyrai known. With regard to origin, all elzevyrai in the collection are divided into four main groups. The first proviniential group consists of Koenigsberg elzevyrai – the books from the library of Prussian King Friedrich Wilhelm I, Royal and university library, as well as the private library of Friedrich August Gotthold, the rector of Friedrich College. The second proviniential group – the books from the libraries of the former Samogitian seminary and Samogitian chapter, based on the book collection of reverend Jonas Chrizostomas Gintila, administrator of the Samogitian diocese. The third and fourth proviniential groups consist of elzevyrai from the former libraries of Vilnius diocese seminary and Vilnius evangelical reformers’ synod.